Keefektivan Metode Penyuluhan Keliling dan Metode Penyuluhan Individu Terhadap Perilaku Kepatuhan Protokol Kesehatan di Kelurahan Sekayu - Diah Lestari Rahmawati; Oktia Woro Kasmini Handayani; Dyah Rini Indriyanti (Poltekkes Kemenkes Padang, 2022)
During the Covid-19 pandemic, efforts are needed to improve people's behavior, one of which is counseling. Several extension methods that can be used are the mobile method and the individual method. Counseling is intended to be able to change people's behavior for the better regarding the Covid-19 health protocol. The purpose of this study was to analyze the effectiveness of individual counseling and mobile counseling methods on behavior change (practice) for compliance with health protocols. This research is experimental research with a pre-test and post-test group design.The population this research is residents of Sekayu Village, Semarang City as of August 2020. The sample used is 100 samples (50 mobile counseling methods, 50 individual counseling methods) with a purposive sampling technique. The data analysis used was univariate analysis, bivariate analysis, to determine differences in community behavior before and after treatment, the Wilcoxon test was used. To find out the difference in the effectiveness of the use of individual and mobile extension methods, the Mann Whitney test was used. The results showed that there were differences in people's behavior regarding the Covid-19 health protocol before and after being given counseling using the mobile counseling method and the individual method. The individual extension method is more effective than the mobile extension method. It’s advisable for health service providers to use individual methods in conducting health education or learning in the community.